Correlation Between Pre-Operating Patient Anxiety and Increasing Blood Glucose in Patients with Diabetes Mellitus at X Room in X Hospital Sukabumi - Safariyah, Erna; Danismaya, Irawan; Lidiyawati, Herlina; Akbar, Rizki Abdullah (KnE Life Sciences, 2021)
Patients who are going for surgery usually experience anxiety. This can cause physiological responses including palpitations, increased blood pressure, pulse, and also breathing difficulties. For patients with Diabetes Mellitus, anxiety can increase blood glucose levels. This condition can cause delays in surgery, and could potentially increase the patient care costs during their stay in hospital. This research aims to explore the correlation between heightened anxiety and blood glucose levels amongst patients with Diabetes Mellitus. This research used a correlation study with cross sectional approach, with 22 respondents. The technique selection of respondents are using accidental sampling. The validity test of Zung Rating Anxiety Scale 0.85 and the reliability value of 0.79. Bivariate analysis used the Spearmen test. Research concluded that most of respondents had mild anxiety level (59,1%) while some respondents experience normal anxiety (40,9%). Most of the respondents had high glucose levels (68.2%), while some respondents had normal glucose levels (31,8%). The results of the Spearman test revealed P-value = 0.041. Based on the research concluded that there is a correlation between pre-operation anxiety and blood glucose levels amongst patients with Diabetes Mellitus. It is recommended that nurses act to prevent or reduce anxiety in this patient demographic. Keywords: Anxiety level, Glucose Level, Diabetes Mellitus